Analisis Transaksi Jual Beli Yang Menggunakan Bitcoin Sebagai Alat Pembayaran - Melia Melia; Christine S.T. Kansil (Jurnal Hukum Adigama, 2022)
Human beings are social creatures (cannot live alone), so they must live in society. Humans, who cannot live without their daily needs, engage in buying and selling activities. With the advent of technology, buying and selling is now done electronically. However, recently the situation has changed with the emergence of virtual payments. One type of virtual currency is bitcoin. In this essay, the author investigates the validity of buying and selling transactions using crypto assets as a means of payment in Indonesia? and the responsibility of the Indonesian government towards buying and selling using crypto assets as a means of payment in Indonesia? Answering the issues in this essay, the author uses a normative research method, a descriptive research nature, using primary, secondary, and tertiary data types, using a legal approach, data collected, processed and analyzed qualitatively. The results of this analysis show that the validity of buying and selling transactions using bitcoin as a means of payment in Indonesia is not valid and is only used as an investment suggestion, so the government must clearly provide warnings/sanctions in Article 33 Paragraph (1) of Law Number 7 of 2011 on Currency and be responsible for regulating the supervision of the use of bitcoin, about standards such as Know Your Customer, money laundering, risks faced by the public, and standardization regarding security systems, and the public should be careful and cautious in activities in the digital world and not accept any other payments except for the legitimate currency in Indonesia (rupiah).